To solve for \( x \) in the equation \( x + 0.60(15) + 0.80(x + 15) = 0 \):
-
First, let's break down the equation step by step.
-
Calculate \( 0.60(15) \):
\[ 0.60 \times 15 = 9 \]
-
Now, rewrite the equation with that value substituted in:
\[ x + 9 + 0.80(x + 15) = 0 \]
-
Next, distribute the \( 0.80 \):
\[ 0.80(x + 15) = 0.80x + 12 \]
-
Substitute that back into the equation:
\[ x + 9 + 0.80x + 12 = 0 \]
-
Combine like terms:
\[ (1 + 0.80)x + (9 + 12) = 0 \]
\[ 1.80x + 21 = 0 \]
-
Now, solve for \( x \):
\[ 1.80x = -21 \]
\[ x = \frac{-21}{1.80} \]
\[ x = -11.67 \]
Since this does not yield any of the multiple-choice answers provided (A: 99, B: 1212, C: 1313, D: 15), it appears there may have been an error in interpreting the equation or the provided options.
Please confirm if this is the correct equation or if there are any additional details.